Micron silicon slurry, micron silicon-carbon negative electrode slurry, preparation method of micron silicon-carbon negative electrode slurry, negative electrode plate, lithium ion battery and electric equipment

By using micron silicon slurry and lithium replenishing binder, the uniform dispersion of micron silicon powder and the improvement of bonding strength are achieved, the problems of low lithium storage capacity and safety hazards of traditional graphite negative electrode materials are solved, and the energy density and circulation performance of lithium-ion batteries are improved.

CN119674083APending Publication Date: 2025-03-21EPNO (SHENZHEN) NEW ENERGY TECHNOLOGY GROUP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510042571.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Traditional graphite negative electrode materials have low lithium storage capacity and low lithium embedded potential, which leads to difficulty in charging at high rates and poses safety hazards, and cannot meet the requirements of high power and high capacity of future automotive lithium-ion batteries.

Method used

Micron silicon slurry is used to prepare a micron silicon carbon negative electrode slurry for the preparation of negative electrode sheets and lithium-ion batteries by adding lithium-added binder and dispersant.

Benefits of technology

It improves the energy density of lithium-ion batteries, enhances the circulation performance of the negative electrode material, alleviates the "island" effect caused by the expansion of silicon particles, and improves the coulomb efficiency and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674083A_ABST
    Figure CN119674083A_ABST
Patent Text Reader

Abstract

The invention provides micron silicon slurry, micron silicon carbon negative electrode slurry, a preparation method of the micron silicon carbon negative electrode slurry, a negative electrode plate, a lithium ion battery and electric equipment, and relates to the field of lithium ion batteries. The micron silicon slurry comprises the following raw materials in parts by weight: 3-7 parts of a lithium supplementing binder, 0.3-1 part of a dispersing agent, 4 parts of micron silicon powder and 88.7-95 parts of a solvent, the lithium-supplementing binder comprises a polyacrylic acid-based polymer containing carboxyl functional groups and lithium. Different from the powder form of the traditional silicon-based negative electrode, the invention directly provides the micron silicon slurry, the micron silicon slurry can be directly applied to the current negative electrode slurry mixing process, and the dispersing agent and the lithium-supplementing binder are added, so that the lithium-supplementing effect is improved. When the micron silicon slurry is used, the problems of dispersion difficulty and bonding strength of micron silicon do not need to be considered too much.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium-ion batteries, and in particular to a micron silicon slurry, a micron silicon-carbon negative electrode slurry and a preparation method thereof, a negative electrode sheet, a lithium-ion battery and an electrical device. Background Art

[0002] At present, with the rapid development of electronic technology and new energy vehicles, electronic and power products are becoming increasingly miniaturized and lightweight. The domestic and foreign markets have increasingly close demands for improving the energy density of lithium-ion batteries. While people are constantly seeking and improving the specific capacity of the positive electrode, they are also constantly seeking and improving the specific capacity of the negative electrode to improve the energy density of lithium-ion batteries.

[0003] Traditional graphite-based negative electrode materials have a low lithium storage capacity (372mAh / g), and their lithium insertion potential is low, very close to the potential of metallic lithium, which makes high-rate charging difficult and poses a safety hazard. Currently, lithium-ion batteries using graphite-based negative electrode materials cannot meet the high-power, high-capacity and other requirements of future automotive lithium-ion batteries.

[0004] Silicon (Si) is considered to be an advanced alternative to graphite anodes because of its higher mass specific capacity (Li 3.75 Si, ~3579mAh g -1 ) and volumetric capacity (>2000mAh cm -3 ), the existing technology usually uses silicon-carbon composite materials as the negative electrode active material of lithium-ion batteries. In order to overcome the expansion effect of silicon-based materials, the materials generally use micro-nano and composite methods to reduce the expansion of materials to achieve the purpose of improving the cycle. Compared with nano silicon powder, micro silicon powder is more favored by the industry due to its wide material source, low processing cost and better stacking density, but due to its special morphological characteristics, it has the following disadvantages in practical applications:

[0005] (1) Micronized silicon powder has a much larger particle size than conventional graphite negative electrode and is very easy to agglomerate. After mixing with graphite, conventional double planetary stirring cannot fully disperse it.

[0006] (2) After the particles agglomerate, the expansion effect during the charge and discharge process intensifies, causing the material to fall off and lose its conductive connection, forming an "island effect" that causes the negative electrode material to fail;

[0007] (3) Conventional styrene-butadiene latex adhesive (SBR) binder systems do not have good adhesion to silicon materials;

[0008] (4) During the battery cycle, the continuous shrinkage and expansion of the silicon negative electrode leads to the pulverization of the silicon negative electrode. The new interface generated by the pulverization continuously consumes lithium ions to produce SEI film.

[0009] The above problems greatly reduce the cycle performance of silicon negative electrode in the battery, which has a crucial impact on the electrochemical performance of micron silicon materials. Summary of the invention

[0010] The purpose of the present application is to provide a micron silicon slurry, a micron silicon-carbon negative electrode slurry and a preparation method thereof, a negative electrode sheet, a lithium-ion battery and an electrical device to solve the above-mentioned problems.

[0011] To achieve the above objectives, the present application provides a micron silicon slurry in a first aspect, wherein the raw materials thereof, measured by weight, include:

[0012] 3-7 parts of lithium supplement binder, 0.3-1 parts of dispersant, 4 parts of micron silicon powder and 88.7-95 parts of solvent;

[0013] The lithium supplementing binder includes a polyacrylic acid-based polymer containing a carboxyl functional group and lithium.

[0014] Optionally, the micron silicon slurry satisfies at least one of the following conditions:

[0015] A. The monomer of the polyacrylic acid-based polymer contains ≥3 hydroxyl groups, the molecular weight of the polyacrylic acid-based polymer is greater than 10,000, and the mass content of lithium element is ≥2%;

[0016] B. the dispersant comprises sodium carboxymethyl cellulose;

[0017] C. The particle size of the micron silicon powder is 0.5 μm-2 μm;

[0018] D. The solvent includes water.

[0019] The second aspect of the present application provides a method for preparing a micron silicon slurry, comprising:

[0020] The raw materials are mixed to obtain micron silica gel liquid;

[0021] The micron silica gel liquid is sheared and dispersed to obtain micron silica slurry.

[0022] Optionally, the linear speed of the shear dispersion is 25m / s-30m / s.

[0023] The third aspect of the present application provides a micron silicon-carbon negative electrode slurry, wherein the raw materials thereof, calculated based on the total mass of 100%, include:

[0024] The micron silicon slurry accounts for 15%-50%, graphite accounts for 40%-80%, and the remaining auxiliary materials and solvents account for less than 15%.

[0025] Optionally, the auxiliary material includes a conductive agent, and the conductive agent carbon black and / or single-walled carbon nanotube conductive paste meets at least one of the following conditions:

[0026] A. the carbon black comprises carbon black Super-p;

[0027] B. The solid content of the single-walled carbon nanotube conductive slurry is 0.4%-2%, and the viscosity is 9000cP-20000cP;

[0028] C. The diameter of the single-walled carbon nanotubes in the single-walled carbon nanotube conductive paste is 0.6 nm-10 nm, and the length is 5 μm-30 μm.

[0029] The fourth aspect of the present application provides a method for preparing the micron silicon-carbon negative electrode slurry, comprising:

[0030] The micron silicon-carbon negative electrode slurry is prepared by mixing the raw materials.

[0031] The fifth aspect of the present application provides a negative electrode plate, comprising the above-mentioned micron silicon-carbon negative electrode slurry.

[0032] A sixth aspect of the present application is a lithium-ion battery, comprising the negative electrode plate.

[0033] A seventh aspect of the present application is an electrical device comprising the lithium-ion battery.

[0034] Compared with the prior art, the beneficial effects of this application include:

[0035] The micron silicon slurry provided in the present application is different from the powder form of traditional silicon-based negative electrodes. The present application directly provides a micron silicon slurry, which can be directly applied to the current negative electrode slurry process, and is added with a dispersant and a lithium-supplementing binder, so that the micron silicon slurry does not need to consider the dispersion difficulty and bonding strength of the micron silicon too much when using it. In addition, the lithium-supplementing effect of the lithium-supplementing binder can release some lithium ions during the cycle to alleviate the lithium ion loss caused by the SEI breakage on the silicon surface, thereby achieving the effect of improving the cycle, and also improving the bonding effect of the micron silicon slurry in the negative electrode application, alleviating the "island" effect caused by the expansion of silicon particles during the cycle.

[0036] The method for preparing the micron silicon slurry provided in the present application realizes uniform dispersion of micron silicon in the micron silicon slurry through shear dispersion, and the operation is simple.

[0037] The micron silicon-carbon negative electrode slurry provided in the present application makes up for the defect of insufficient adhesion of the conventional negative electrode binder system (SBR+CMC) to the micron silicon particles due to the presence of the polyacrylic acid binder in the micron silicon slurry.

[0038] The preparation method of the micron silicon-carbon negative electrode slurry provided in the present application can easily obtain a micron silicon-carbon negative electrode slurry with a high capacity density by using the above-mentioned micron silicon slurry in combination with the current slurry mixing method. When using the micron silicon slurry, which is a silicon-containing raw material, there is no need to consider the dispersion difficulty and bonding strength of the micron silicon too much, and the preparation method is simple.

[0039] The negative electrode plate provided in the present application has uniformly dispersed internal particles and good bonding strength, which can effectively suppress the expansion changes of the negative electrode plate during the charge and discharge cycle. Therefore, there is no need to consider changing the binder system during use. In addition, its unique synergistic lithium replenishment effect enables the plate to obtain a better cycle life.

[0040] The lithium-ion battery and electrical equipment provided in this application have high coulombic efficiency and good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0042] Figure 1 The SEM images of the micron silicon raw materials used in the examples and comparative examples;

[0043] Figure 2 is an X-ray photoelectron spectrum of the micron silicon raw material used in the embodiments and comparative examples;

[0044] Figure 3 A schematic diagram of the preparation process of the micron silicon slurry provided in Example 1;

[0045] Figure 4 A schematic diagram of the preparation process of the micron silicon-carbon negative electrode slurry and the negative electrode sheet provided in Example 1;

[0046] Figure 5 1C / 1C cycle curves of lithium ion batteries prepared in Examples 1-3 and Comparative Examples 1-3;

[0047] Figure 6 This is a SEM comparison picture of the silicon-carbon negative electrode sheets of Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0048] As used herein:

[0049] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0050] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0051] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0052] In these examples, parts and percentages are by mass unless otherwise indicated.

[0053] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0054] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0055] The first aspect of the present application provides a micron silicon slurry, the raw materials of which, measured by weight, include:

[0056] 3-7 parts of lithium supplement binder, 0.3-1 parts of dispersant, 4 parts of micron silicon powder and 88.7-95 parts of solvent;

[0057] The raw materials of the micron silicon slurry are measured by weight: the lithium supplement binder can be 3 parts, 4 parts, 5 parts, 6 parts, 7 parts or any value between 3 parts and 7 parts; the dispersant can be 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts or any value between 0.3 parts and 1 parts; the solvent can be 88.7 parts, 89 parts, 90 parts, 91 parts, 92 parts, 93 parts, 94 parts, 95 parts or any value between 88.7 parts and 95 parts;

[0058] The lithium supplementing binder is a polyacrylic acid-based polymer with partially lithiated carboxyl functional groups.

[0059] It should be noted that the lithium-supplemented binder undergoes lithiation in which the H in the carboxyl functional group is replaced by Li, i.e. -COOli.

[0060] It should also be noted that the addition of polyacrylic acid binder and dispersant ensures the stability of micron silicon dispersion in the slurry.

[0061] In some embodiments, the micron silicon slurry satisfies at least one of the following conditions:

[0062] A. The monomer of the polyacrylic acid-based polymer contains ≥3 hydroxyl groups, the molecular weight of the polyacrylic acid-based polymer is greater than 10,000, and the mass content of lithium element is ≥2%;

[0063] Optionally, the number of hydroxyl groups in the monomer of the polyacrylic acid-based polymer may be 3, 10, 15, 20, 25, 30, 40, 50 or greater than or equal to 3, the molecular weight of the polyacrylic acid-based polymer may be 11000, 15000, 20000, 30000 or any value greater than 10000, and the mass content of lithium element may be 2%, 5%, 10%, 20%, 30% or any value greater than or equal to 2%;

[0064] B. the dispersant comprises sodium carboxymethyl cellulose;

[0065] C. The particle size of the micron silicon powder is 0.5 μm-2 μm;

[0066] Optionally, the particle size of the micron silicon powder may be 0.5 μm, 1 μm, 1.5 μm, 2 μm or any value between 0.5 μm and 2 μm;

[0067] D. The solvent includes water.

[0068] The second aspect of the present application provides a method for preparing a micron silicon slurry, comprising:

[0069] The raw materials are mixed to obtain micron silica gel liquid;

[0070] The micron silica gel liquid is sheared and dispersed to obtain micron silica slurry.

[0071] In some embodiments, shear dispersion is achieved by uniformly dispersing micron silicon materials through a cycloidal high-speed dispersion device, such as a cycloidal high-speed disperser. The main principle of dispersion is to rely on the strong shear force generated by the high linear speed of the rotor inside the device to break up particle agglomerations and achieve uniform dispersion of particles in the liquid.

[0072] In some embodiments, the linear velocity of the shear dispersion is 25 m / s-30 m / s.

[0073] Optionally, the linear velocity of shear dispersion can be 25 m / s, 26 m / s, 27 m / s, 28 m / s, 29 m / s, 30 m / s or any value between 25 m / s and 30 m / s.

[0074] In some embodiments, the linear velocity of shear dispersion refers to the linear velocity of the rotor in the relevant shear dispersion equipment, and the flow rate of the shear dispersed micron silicon slurry is 1 L / min.

[0075] The third aspect of the present application provides a micron silicon-carbon negative electrode slurry, wherein the raw materials thereof, calculated based on the total mass of 100%, include:

[0076] The micron silicon slurry accounts for 15%-50%, graphite accounts for 40%-80%, and the remaining auxiliary materials and solvents account for less than 15%.

[0077] Optionally, the raw materials of the micron silicon-carbon negative electrode slurry are calculated based on the total mass of 100%, the micron silicon slurry can be 15%, 20%, 30%, 40%, 50% or any value between 15% and 50%, the graphite can be 40%, 50%, 60%, 70%, 80% or any value between 40% and 80%, and the remaining auxiliary materials and solvents can be 1%, 5%, 10%, 14% or any value between <15%.

[0078] It should be noted that the micron silicon slurry as a raw material is directly involved in the traditional negative electrode slurry process to obtain the micron silicon-carbon negative electrode slurry, and the micron silicon-carbon negative electrode slurry can be obtained using traditional double planetary mixing equipment.

[0079] In some embodiments, the auxiliary material includes a conductive agent, and the conductive agent carbon black and / or single-walled carbon nanotube conductive paste meets at least one of the following conditions:

[0080] A. the carbon black comprises carbon black Super-p;

[0081] B. The solid content of the single-walled carbon nanotube conductive slurry is 0.4%-2%, and the viscosity is 9000cP-20000cP;

[0082] Optionally, the solid content of the single-walled carbon nanotube conductive paste can be 0.4%, 0.5%, 1%, 1.5%, 2% or any value between 0.4% and 2%, and the viscosity can be 9000cP, 10000cP, 15000cP, 20000cP or any value between 9000cP and 20000cP;

[0083] C. The diameter of the single-walled carbon nanotubes in the single-walled carbon nanotube conductive paste is 0.6 nm-10 nm, and the length is 5 μm-30 μm.

[0084] Optionally, the diameter of the single-walled carbon nanotubes in the single-walled carbon nanotube conductive paste can be 0.6nm, 1nm, 5nm, 10nm or any value between 0.6nm and 10nm, and the tube length can be 5μm, 10μm, 15μm, 20μm, 25μm, 30μm or any value between 5μm and 30μm.

[0085] The fourth aspect of the present application provides a method for preparing the micron silicon-carbon negative electrode slurry, comprising:

[0086] The micron silicon-carbon negative electrode slurry is prepared by mixing the raw materials.

[0087] The fifth aspect of the present application provides a negative electrode plate, comprising the above-mentioned micron silicon-carbon negative electrode slurry.

[0088] A sixth aspect of the present application is a lithium-ion battery, comprising the negative electrode plate.

[0089] A seventh aspect of the present application is an electrical device comprising the lithium-ion battery.

[0090] It should be noted that electrical equipment may be but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc.; among them, mobile devices may include but are not limited to at least one of mobile phones, laptop computers, etc.; electric vehicles may include but are not limited to at least one of pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.

[0091] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0092] The micron silicon raw material used in the embodiments and comparative examples is industrial photovoltaic silicon waste, and is crushed and sieved to obtain silicon powder material with a size range of 0.5 μm-2 μm. The SEM of the micron silicon powder is as follows: Figure 1 As shown, the X-ray photoelectron spectrum is Figure 2 shown.

[0093] The monomer of the polyacrylic acid-based polymer used in the examples and comparative examples contains 5 hydroxyl groups, a molecular weight of 10,000 to 25,000, and a lithium content of 3% by mass, and is purchased from Fujian Blue Ocean Black Stone New Material Technology Co., Ltd.

[0094] The single-walled carbon nanotube conductive slurry used in the examples and comparative examples has a solid content of 0.8% and a viscosity of 12000 cP. The diameter of the single-walled carbon nanotube is 0.6 nm-10 nm and the length is 5 μm-30 μm. It is purchased from Oakseaer Trading (Shenzhen) Co., Ltd.

[0095] Example 1

[0096] The first aspect of the present embodiment provides a micron silicon slurry and a preparation method thereof, specifically comprising:

[0097] Step 1: Add 0.5 parts of sodium carboxymethyl cellulose to 90.5 parts of deionized water according to the mass ratio, stir at 2000 rpm for 30 minutes, and after the sodium carboxymethyl cellulose powder is completely dissolved, add 5 parts of polyacrylic acid-based polymer, and continue stirring at 2000 rpm for 30 minutes to obtain an adhesive glue solution;

[0098] Step 2: Add 4 parts of micron silicon powder to the above adhesive solution, and stir at 2000 rpm for 60 minutes to obtain micron silicon liquid;

[0099] Step 3: The micron silica gel liquid obtained in step 2 is transported to a gyratory high-speed disperser through a pipeline connection for high-speed dispersion treatment. The high-speed disperser is set to a rotor linear speed of 30 m / s and treated at a speed of 1 L / min for 3 hours to obtain a micron silicon slurry.

[0100] The preparation process of the micron silicon slurry is as follows: Figure 3 shown.

[0101] The second aspect of this embodiment provides a micron silicon-carbon negative electrode slurry and a preparation method thereof, specifically comprising:

[0102] Step 4: Take the micron silicon slurry prepared in step 3 and the carbon black Super-p conductive agent and add them into a planetary mixer with an orbital speed of 55 rpm and a dispersion speed of 4500 rpm and stir them at a high speed in a vacuum for 40 minutes;

[0103] Step 5: Continue to add graphite to the planetary mixer, and stir at a revolution speed of 55 rpm and a dispersion speed of 4000 rpm under vacuum for 50 minutes; then continue to add single-walled carbon nanotube conductive slurry and stir at a revolution speed of 55 rpm and a dispersion speed of 4500 rpm under vacuum for 30 minutes. After stirring, add deionized water to adjust the viscosity to a qualified value (2000-6000 MPa·s). The final slurry viscosity obtained in this embodiment is 4550 MPa·s.

[0104] Step 6: Finally, add the styrene-butadiene rubber latex into the planetary mixer, slowly stir and sieve under vacuum to obtain the micron silicon negative electrode slurry. The mass ratio of micron silicon slurry, carbon black Super-p conductive agent, single-walled carbon nanotube conductive slurry, graphite and styrene-butadiene rubber latex used in steps 4-6 is: 47.73:3.11:0.50:45.56:3.11.

[0105] A third aspect of this embodiment provides a negative electrode sheet, wherein the micron silicon-carbon negative electrode slurry obtained in step 6 is applied to a current collector copper foil and dried to obtain a micron silicon-carbon material negative electrode sheet.

[0106] The preparation process of the micron silicon carbon negative electrode slurry and the negative electrode sheet is as follows: Figure 4 shown.

[0107] Example 2

[0108] The first aspect of the present embodiment provides a micron silicon slurry and a preparation method thereof, specifically comprising:

[0109] Step 1: Add 0.3 parts of sodium carboxymethyl cellulose to 88.7 parts of deionized water according to the mass ratio, stir at 2000 rpm for 30 minutes, and after the sodium carboxymethyl cellulose powder is completely dissolved, add 7 parts of polyacrylic acid-based polymer, and continue stirring at 2000 rpm for 30 minutes to obtain an adhesive glue solution;

[0110] Step 2: Add 4 parts of micron silicon powder material to the above adhesive glue solution, stir at 2000 rpm for 60 minutes to obtain micron silicon liquid;

[0111] Step 3: The micron silica gel liquid obtained in step 2 is transported to a gyratory high-speed disperser through a pipeline connection for high-speed dispersion treatment. The high-speed disperser is set to a rotor linear speed of 30 m / s and treated at a speed of 1 L / min for 3 hours to obtain a micron silicon slurry.

[0112] The second aspect of this embodiment provides a micron silicon-carbon negative electrode slurry and a negative electrode plate, the preparation method of which is consistent with that of Example 1, except that the micron silicon slurry is replaced by the micron silicon slurry prepared in this embodiment.

[0113] Example 3

[0114] The first aspect of the present embodiment provides a micron silicon slurry and a preparation method thereof, specifically comprising:

[0115] Step 1: Add 0.7 parts of sodium carboxymethyl cellulose to 92.3 parts of deionized water according to the mass ratio, stir at 2000 rpm for 30 minutes, and after the sodium carboxymethyl cellulose powder is completely dissolved, add 3 parts of polyacrylic acid-based polymer, and continue stirring at 2000 rpm for 30 minutes to obtain an adhesive glue solution;

[0116] Step 2: Add 4 parts of micron silicon powder material to the above adhesive glue solution, stir at 2000 rpm for 60 minutes to obtain micron silicon liquid;

[0117] Step 3: The micron silica gel liquid obtained in step 2 is transported to a gyratory high-speed disperser through a pipeline connection for high-speed dispersion treatment. The high-speed disperser is set to a rotor linear speed of 30 m / s and treated at a speed of 1 L / min for 3 hours to obtain a micron silicon slurry.

[0118] The second aspect of this embodiment provides a micron silicon-carbon negative electrode slurry and a negative electrode plate, the preparation method of which is consistent with that of Example 1, except that the micron silicon slurry is replaced by the micron silicon slurry prepared in this embodiment.

[0119] Comparative Example 1

[0120] The first aspect of this comparative example provides a micron silicon slurry and a preparation method thereof, specifically comprising:

[0121] Step 1: Add 1 part of sodium carboxymethyl cellulose to 95 parts of deionized water according to the mass ratio, and stir at 2000 rpm for 30 minutes to obtain an adhesive glue solution;

[0122] Step 2: Add 4 parts of micron silicon powder material to the above adhesive glue solution, stir at 2000 rpm for 60 minutes to obtain micron silicon liquid;

[0123] Step 3: The micron silica gel liquid obtained in step 2 is transported to a gyratory high-speed disperser through a pipeline connection for high-speed dispersion treatment. The high-speed disperser is set to a rotor linear speed of 30 m / s and treated at a speed of 1 L / min for 3 hours to obtain a micron silicon slurry.

[0124] The second aspect of this comparative example provides a micron silicon-carbon negative electrode slurry and a negative electrode plate, the preparation method of which is consistent with that of Example 1, except that the micron silicon slurry is replaced by the micron silicon slurry prepared in this comparative example.

[0125] Comparative Example 2

[0126] The difference from Example 1 is that the high-speed dispersion process in step 3 is not performed.

[0127] The SEM comparison of the silicon-carbon negative electrode sheets of Example 1 and Comparative Example 2 is shown in Figure 6 shown.

[0128] Comparative Example 3

[0129] The difference from comparative example 1 is that the high-speed dispersion treatment in step 3 is not performed. Microsilicon powder is directly added to a double planetary mixer to participate in the preparation of negative electrode slurry; the preparation method specifically includes:

[0130] Step 1: Add 1 part of sodium carboxymethyl cellulose (CMC) to 95 parts of deionized water and stir at 2000 rpm for 30 minutes to obtain CMC glue;

[0131] Step 2: Take the obtained CMC glue and add it to the planetary mixer, then add the micron silicon powder and carbon black Super-p conductive agent into the planetary mixer, with the revolution speed of 55rpm and the dispersion speed of 4500rpm under vacuum high-speed stirring for 40min;

[0132] Step 3: Continue to add graphite to the planetary mixer, and stir at a revolution speed of 55 rpm and a dispersion speed of 4000 rpm under vacuum for 50 minutes; then continue to add single-walled carbon nanotube conductive slurry and stir at a revolution speed of 55 rpm and a dispersion speed of 4500 rpm under vacuum for 30 minutes. After stirring, add deionized water to adjust the viscosity to a qualified value (2000-6000 MPa·s). The final slurry viscosity obtained in this embodiment is 4890 MPa·s.

[0133] Step 4: Finally, add the styrene-butadiene rubber latex into the planetary mixer, slowly stir and sieve under vacuum to obtain the micron silicon negative electrode slurry. The mass ratio of micron silicon powder, CMC glue, carbon black Super-p conductive agent, single-walled carbon nanotube conductive slurry and styrene-butadiene rubber latex used in steps 2 to 4 is: 1.91:45.82:3.11:0.50:45.56:3.11.

[0134] A third aspect of this embodiment provides a negative electrode sheet, wherein the micron silicon-carbon negative electrode slurry obtained in step 4 is applied to a current collector copper foil and dried to obtain a micron silicon-carbon material negative electrode sheet.

[0135] Comparative Example 4

[0136] The difference from Example 1 is that the polyacrylic acid-based polymer is replaced by a conventional polyacrylic acid (non-lithiated) adhesive purchased from Fujian Blue Ocean Black Stone New Material Technology Co., Ltd.

[0137] The negative electrode plates prepared in the above embodiments and comparative examples were assembled with the ternary material positive electrode plates into soft-pack lithium-ion batteries, and the initial efficiency, electrode plate expansion and cycle tests of the lithium battery were carried out (the cycle test conditions were 1C / 1C, 2.5V~4.2V, and the ambient temperature was 25±3°C). The specific test results are shown in Table 1.

[0138] Table 1 Performance test

[0139]

[0140] analyze:

[0141] It can be seen from the results in Table 1 that the cycle performance of the embodiment is significantly better than that of the comparative example, and the pole piece expansion rate of the embodiment is also better than that of the comparative example under the same number of cycles.

[0142] Combined with the electron microscope photo of the pole piece of Example 1 ( Figure 5 Left) and Comparative Example 2 ( Figure 5 (Right) From the comparison of the electron microscope photos of the electrode pieces, it can be seen that the agglomeration of micron silicon particles on the negative electrode piece basically disappears when the micron silicon slurry that has been subjected to high-speed dispersion treatment is used, and a better dispersion effect is achieved. On the other hand, in Example 2, although the two use the same component formula and use micron silicon slurry that has not been subjected to high-speed dispersion treatment, the agglomeration effect of the micron silicon particles in the negative electrode piece is very obvious, and the year-on-year expansion rate of the electrode piece is also significantly higher than that of Example 1, indicating that the expansion effect of the silicon particles caused by agglomeration is amplified, thereby causing the attenuation of the battery cycle to increase and plunge. The attenuation trend of the battery in the example using the high-speed dispersion process gradually slows down in the later stage of the cycle, and the cycle performance is also greatly improved. Its cycle life is increased by 300% compared with that of Example 1. Similarly, a similar conclusion can be drawn by comparing Example 1 with Example 3.

[0143] Comparing the examples, we found that changing the ratio of polyacrylic acid-based polymer to sodium carboxymethyl cellulose in the micron silicon slurry has a greater impact on the cycle results. The cycle performance and expansion rate performance of the three groups of examples using polyacrylic acid-based polymers are better than those of comparative example 1 (polyacrylic acid-based polymers are not used in the component formula). Comparing the expansion rate data of 50 cycles, we found that the addition of polyacrylic acid-based polymers has a significant mitigating effect on the full-charge expansion of the pole piece. Example 2 with the largest addition amount showed the smallest expansion rate, and comparative example 1 without polyacrylic acid-based polymers had the largest expansion rate, which is consistent with the pole piece peeling strength test results in the table. The addition of polyacrylic acid-based polymers does improve the peeling strength of the pole piece and the bonding effect between the powder and the pole piece, thereby effectively suppressing the expansion effect of the pole piece. However, Example 1 with a slightly worse pole piece expansion rate showed the best cycle performance, indicating that the improvement of the battery cycle performance of the prepared micron silicon-carbon material negative pole piece is the synergistic effect of the binder and the components.

[0144] Comparing the first charge and discharge efficiency data of all the above case batteries, the first efficiency data of Examples 1 to 3 using lithiated polyacrylic acid-based polymers are generally higher than that of Comparative Example 1 without addition, among which the first efficiency of Example 2 is about 1% higher. Similarly, compared with Comparative Example 4 using non-lithiated conventional polyacrylic acid-based polymers, the first efficiency of Example 1 is also about 0.6% higher, and the cycle life is also 112 more. This shows that the use of lithiated binders can indeed achieve a certain lithium supplementation effect during the charge and discharge process of the battery, reducing the consumption of lithium ions in the system, thereby showing better cycle performance.

[0145] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0146] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A micron silicon slurry, characterized in that: The raw materials include, by weight: 3-7 parts of lithium supplement binder, 0.3-1 parts of dispersant, 4 parts of micron silicon powder and 88.7-95 parts of solvent; The lithium supplement binder is a polyacrylic acid-based polymer with partially lithiated carboxyl functional groups.

2. The micron silicon slurry according to claim 1, characterized in that: At least one of the following conditions is met: A. The monomer of the polyacrylic acid-based polymer contains ≥3 hydroxyl groups, the molecular weight of the polyacrylic acid-based polymer is greater than 10,000, and the mass content of lithium element is ≥2%; B. the dispersant comprises sodium carboxymethyl cellulose; C. The particle size of the micron silicon powder is 0.5 μm-2 μm; D. The solvent includes water.

3. A method for preparing the micron silicon slurry according to claim 1 or 2, characterized in that: include: The raw materials are mixed to obtain micron silica gel liquid; The micron silica gel liquid is sheared and dispersed to obtain micron silica slurry.

4. The method for preparing micron silicon slurry according to claim 3, characterized in that: The linear speed of the shear dispersion is 25 m / s-30 m / s.

5. A micron silicon-carbon negative electrode slurry, characterized in that: The raw materials thereof, calculated based on the total mass as 100%, include: The micron silicon slurry as claimed in claim 1 or 2 comprises 15%-50%, graphite 40%-80%, and the remaining auxiliary materials and solvents account for less than 15%.

6. The micron silicon-carbon negative electrode slurry according to claim 5, characterized in that: The auxiliary material includes a conductive agent, and the conductive agent carbon black and / or single-walled carbon nanotube conductive paste meets at least one of the following conditions: A. the carbon black comprises carbon black Super-p; B. The solid content of the single-walled carbon nanotube conductive slurry is 0.4%-2%, and the viscosity is 9000cP-20000cP; C. The diameter of the single-walled carbon nanotubes in the single-walled carbon nanotube conductive paste is 0.6 nm-10 nm, and the length is 5 μm-30 μm.

7. A method for preparing the micron silicon-carbon negative electrode slurry according to claim 5 or 6, characterized in that: include: The micron silicon-carbon negative electrode slurry is prepared by mixing the raw materials.

8. A negative electrode plate, characterized in that: Including the micron silicon-carbon negative electrode slurry as described in claim 5 or 6.

9. A lithium ion battery, characterized in that: Including the negative electrode sheet as described in claim 8.

10. An electrical device, characterized in that: Includes the lithium ion battery as claimed in claim 9.